Rapid functional response tests for assessing impacts of alien snails on food crops - N.W. Thunnissen (Elsevier, 2021)
Several invasive alien snails are considered a threat to agriculture and horticulture. The development of rapid methods for reliable prediction of their impacts on crops is a major challenge in agricultural science and invasion biology. The use of comparative functional response tests could give insight in the potential impact of alien herbivorous snails on agricultural crops and natural vegetation. It has been hypothesised that invasive alien snails are superior competitors for resources in comparison with common native species, due to higher attack rates and lower handling times of their food. Applications of the functional response approach to terrestrial snails are scarce, despite offering a convenient test design and delivering meaningful mechanistic understanding of resource use of species. The main objectives of this study were (i) to determine the potential grazing effect of the common garden snail (Cornu aspersum) on some common agricultural crops, using the functional response approach, (ii) to determine whether the presence of an intraspecific and interspecific competitor affects food consumption of this species, and (iii) to assess the interspecific variation in impact for standardization of functional response tests for herbivorous snails. Food consumption of C. aspersum differed significantly for three crops: lettuce (Lactuca sativa), endive (Cichorium endivia var. latifolia) and common corn salad (Valerianella locusta). The functional responses for consumption of Lactuca sativa differed significantly between individuals collected from wild and from cultured populations of C. aspersum. Furthermore, the food consumption (in dry weight) of C. aspersum differed between tests with presence of an intraspecific and interspecific competitor (i.e., C. aspersum and Cepaea nemoralis, respectively). So, the interspecific and intraspecific competition for resources should be considered in risk assessments in order to generate more reliable impact predictions of alien snail species and to improve our understanding of their interactions with other grazers.